Pembuatan Aplikasi Point of Sales untuk Rumah Makan Dapur Rinjani - Herman, Hendy Thomas; Rostianingsih, Silvia; Setiawan, Alexander (Jurnal Infra, 2016)
"Rumah Makan Dapur Rinjani" is a restaurant located in Malang, which offers various Indonesian food. Until now, food ordering, reservation registering, delivering the order to kitchen, and counting the payment bill are still manual, which is not efficient.Web based ordering application which can also be accessed through a local connected mobile devices will be made in this thesis. This application is made from PHP framework Laravel, Javascript, HTML as programming language in web based ordering application, and mySQL for its database.Based on the examination of the system that has been done, the system is able to check the login informationÂ  before entering the system, displays the available order, setting the user and member, registers reservation data, add promotion, updates order status in the kitchen, and displays sales and stock report. This application need local connection to login, ordering food, and updating data.